Preperation and Nutrition study of Complementary baby foods from Cereals & Legumes 1- Using of Bulgur with each of Germination Lentil & Chick pea - Bayan Y. Al – Abdulla; Marwa I . Abd (Tikrit Journal of Pure Science)
This study was carried out to prepare two formulas of complementary baby foods. The first formula formed from bulgur and sprouted Lentil, the second formula formed from bulgur and sprouted chick pea in addition to the other secondary ingredients. Results showed slight difference in protein, fat, ash, carbohydrates and calories between the two formula. The same conclusion may be referred to contents of: amino acids, vitamins and minerals. The results showed that the nutritional value of the two formulas was higher than some local baby foods blends of some countries , and was close to some global and commercial blends specifications .Sensory evaluation revealed to high acceptance of the two formulas [82.5 , 87.4] respectively. Microbial tests showed no growth of coliform bacteria while aerobic total plate count bacteria was within the range of limited number of Iraqi standand specification of baby foods.  Sensory evaluation revealed to high acceptance of the two formulas [82.5, 87.4] respectively.